2013
DOI: 10.1017/thg.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

Medical Record Validation of Maternal Recall of Pregnancy and Birth Events From a Twin Cohort

Abstract: This study aims to assess the validity of maternal recall for several perinatal variables 8–10 years after pregnancy in a twin sample. Retrospective information was collected 8–10 years after the delivery event in a cohort of mothers from the University of Southern California Twin Study (N = 611) and compared with medical records for validity analysis. Recall of most variables showed substantial to perfect agreement (κ = 0.60–1.00), with notable exceptions for specific medical problems during pregnancy (κ ≤ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 59 publications
(107 reference statements)
5
42
0
Order By: Relevance
“…This study attempts to highlight the importance of including perinatal risks while also providing a strategy for compiling perinatal risks into a form that is relatively easy to use. We demonstrate that there is a relatively high level of agreement for self-reports and medical records on most constructs, which is consistent with previous reports (e.g., Liu et al, 2013; Olson et al, 1997), although perinatal events more medical in nature typically show lower agreement with medical records (e.g., Coolman et al, 2010). This report also demonstrates the usefulness of collapsing across multiple specific perinatal risks to create more general indices that represent categories of risk.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study attempts to highlight the importance of including perinatal risks while also providing a strategy for compiling perinatal risks into a form that is relatively easy to use. We demonstrate that there is a relatively high level of agreement for self-reports and medical records on most constructs, which is consistent with previous reports (e.g., Liu et al, 2013; Olson et al, 1997), although perinatal events more medical in nature typically show lower agreement with medical records (e.g., Coolman et al, 2010). This report also demonstrates the usefulness of collapsing across multiple specific perinatal risks to create more general indices that represent categories of risk.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a study of maternal recall 8 to 10 years after pregnancy found high agreement between maternal self-report and medical records for most variables. Yet, the recall for specific medical problems during pregnancy, neonatal intensive care, and post-delivery complications were recalled with low accuracy (Liu, Tuvblad, Li, Raine, & Baker, 2013). Similar patterns of findings were reported in two studies examining self-reports and birth records at 4 months postpartum (Dietz et al, 2014), with better recall for women with a college degree (Bat-Erdene, Metcalfe, McDonald, & Tough, 2013).…”
Section: The Importance Of Measurement Of Perinatal Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Pickett et al (2009), for example, compared SDP data from women that was collected both prospectively (self-report and cotinine) and retrospectively (when children are in adolescence) and suggest that women’s ability to recall their smoking behavior in pregnancy more than a decade after the event is generally both accurate and reliable, particularly for the second and third trimester of pregnancy. Several studies have also compared maternal recall of prenatal events and behaviors to birth or medical records (e.g., Land et al 2012; Liu et al 2013; Neiderhiser et al, under review) in order to assess validity of retrospective recall. In general, these studies suggest very strong agreement between medical records and maternal recall when SDP is a dichotomous yes/no indicator, yet reports still caution against using maternal report as the sole source of information (e.g., Liu et al 2013).…”
Section: Quality Of Sdp Assessment: the Utility Of Multiple Reportersmentioning
confidence: 99%
“…Several studies have also compared maternal recall of prenatal events and behaviors to birth or medical records (e.g., Land et al 2012; Liu et al 2013; Neiderhiser et al, under review) in order to assess validity of retrospective recall. In general, these studies suggest very strong agreement between medical records and maternal recall when SDP is a dichotomous yes/no indicator, yet reports still caution against using maternal report as the sole source of information (e.g., Liu et al 2013). …”
Section: Quality Of Sdp Assessment: the Utility Of Multiple Reportersmentioning
confidence: 99%